Math

What are the like terms in the exprression 3ac = ab - ac = 2ab? Explain.
Simplify the expression. Show your work.

  1. 👍 0
  2. 👎 0
  3. 👁 48
asked by Maddy

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    What are the like terms in this expression. 3ac + ab - ac + 2ab? Explain please?

    asked by Maddy on September 1, 2008
  2. Polynomials

    State whether the following equations are sometimes, always or never true. a) a^2-2ab-b^2= (a-b)^2, bis not equal to 0 b) a^2+ b^2= (a+b)(a+b) c) a^2-b^2= a^2-2ab+b^2 d) (a=b)^2 = a^2+2ab+b^2 I don't understand what these

    asked by Lucina on January 10, 2015
  3. Math

    Combine like terms(same variable to the same power) Simplify: 3a^3b+4a^2b^2-7a^3b+2ab-5a^2b^2+10a^3b

    asked by Sony on February 4, 2016
  4. algebra

    Is this correct? subtract (4a^3+2b^3)-(6a^3+5a^2b-2ab^2+2b^3) answer: -2a^3-5a^2b+2ab^2

    asked by bb on February 6, 2008
  5. algebra

    evaluate the exprression 90/x for the given values of x to complete the table x 2 3 5 9 15 18 20

    asked by James on September 28, 2010
  6. factoring completly

    can anyone help me with these: 3x2 + 17x + 10 5y8 - 125 a2 - 2ab - 15b2 4c2 - 12c + 9 5 y^8 - 125 = 5(y^8 - 25) y^8 - 25 can be written (y^4 - 5)(y^4 + 5) For the others, you need to try a few factors until you find a pair that

    asked by mike on March 9, 2007
  7. math

    Kahlil said that using the equation € (a + b)2 = a2 + 2ab + b2, , he can find a similar equation for € (a − b)2 . Examine his argument. If it is correct, supply any missing steps or justification; If it is incorrect point

    asked by Anonymous on September 26, 2011
  8. math

    Kahlil said that using the equation (a + b)2 = a2 + 2ab + b2, he can find a similar equation for (a - b)2. Examine his argument. (a - b)2 = [a + (-b)]2 = a2 + 2a(-b) + (-b)2 = a2 – 2ab + b2

    asked by jeana on July 3, 2011
  9. Math

    I don't understand how this is if (a ± b)² = a² ± 2ab + b² i would think that is would be A squared plus or minues B squared where does the 2ab come from??

    asked by Jon on August 28, 2007
  10. Maths

    A polynomial g(x) is given by: g(x) = (x-1)(x+2)(x-a)(x-b) 1) Given that g(0)=4 show that ab=-2 2) given also that g(3)=40 show that a+b=1 3) given that a and b are integers, give possible values for a and b. My answers 1) g(0) =

    asked by Anonymous on October 15, 2015

More Similar Questions